The Effect of Story Telling Method on Student's Speaking Skills at The Second Grade of Junior High School - Olin Risnawati Purba; Valews Nopatri L. Purba; Jesie Nuari Simarmata; Natalia Widya Pasca Tarigan (Peneliti.net, 2022)
The study aimed of this research to determine whether the storytelling method affects students' speaking skills. This study used experimental research, which consist of two group, namely, Experimental group and control group. The populations of this research were 20 students and divided became 2 samples each sample consist of 10 students. The experimental group implied Storytelling method and used pre-test, treatment, and post-test while the control group implied conventional method and used pre-test, post-test and no treatment. From this method, the researchers found the difference of implementing the storytelling method towards students’ achievement with the result was satisfying. The result of this research also provided the effectiveness of implementing the storytelling towards student achievement in speaking skill with compare the value that students’ got from post-test and the storytelling method is considered successful. From the result, it is conclude that implementing the storytelling method has and effect toward students’ speaking skill